Spinal cord involvement in two children with posterior reversible encephalopathy syndrome. (October 2017) - Lucchesi, Maurizio; Mascalchi, Mario; Mussa, Federico; Favre, Claudio; Genitori, Lorenzo; Sardi, Iacopo
Spinal cord involvement (SCI) is a rare feature of posterior reversible encephalopathy syndrome (PRES), especially in children. SCI is generally symptomatic, and may have a different outcome compared with encephalic localization of PRES. We reported about two cases of SCI in pediatric patients with PRES, after multimodal anticancer therapies, including radiotherapy, chemotherapy and targeted agents.